Cardiac arrest management in general practice in Ireland: a 5-year cross-sectional study. Issue 5 (14th May 2013) - Bury, G; Headon, M; Egan, M; Dowling, J
Abstract : Objective: To document the involvement of general practitioners (GPs) in cardiac arrests with resuscitation attempts (CARAs) and to describe the outcomes. Design: A 5-year prospective cross-sectional study of GPs in Ireland equipped with automated external defibrillators (AEDs) and immediate care training by the MERIT Project, with data collection every 3 months over the 5-year period. Practices reported CARAs by quarterly survey with an 89% mean response rate (81–97% for the period). Setting: General practices throughout Ireland. Participants: 495 GP participated: 168 (33.9%) urban, 163 (32.9%) rural and 164 (33.1%) mixed. Interventions: All participating practices received a standard AED and basic life support kit. Training in immediate care was provided for at least one GP in the practice. Main outcome measures: Incidence of CARA in participating practices. Return of spontaneous circulation (ROSC) and discharge alive from hospital. Results: 36% of practices were involved in a CARA during the 5-year period and 13% were involved in more than one CARA. Of the 272 CARAs reported, ROSC occurred in 32% (87/272) and discharge from hospital in 18.7% (49/262). In 45% of cases, the first AED was brought by the GP and in 65%, the GP arrived before the ambulance service. More cases occurred in rural and mixed settings than urban ones, but the survival rates did not differ between areas. In 65% of cases, the GP was on duty at the time of the incident and 47% of cases occurred in the patient's home. Conclusions: These outcomes are comparable with more highly structured components of the emergency response system and indicate that GPs have an important role to play in the care of patients in their own communities. GPs experience cardiac arrest cases during the course of their daily work and provide prompt care which results in successful outcomes in urban, mixed and rural settings.